MATHCAD INFORMATION EDUCATIONAL TECHNOLOGIES ON THE BASIS OF INTEGRATION OF ACTIONSCRIPT PROGRAMS AND THE MATHCAD - Gennady Valentinovich Alekseev; Anatoly Anatolyevich Khripov (Современная наука и инновации)
In the article a new concept of a creation of e-learning materials in universities (lectures, laboratory works) on the basis of an integration of Adobe Flash Actionscript animation programming language and Mathcad package is proposed. A new e-learning laboratory work “Cake filtration in a presence of sedimentation” is presented as the example of the concept.